'Isifazane Sakiti Emadolobheni' (Our Women in the Towns): The Politics of Gender in Ilanga lase Natal, 1933-1938 - du Toit, Marijke; Nzuza, Palesa (The Journal of Natal and Zulu history, 2019)
In this article we consider the gender dimensions of the public forum that was constituted, mostly in isiZulu, through Ilanga lase Natal at a time when increasing numbers of African women were migrating to and settling in Durban. At the start of the 1930s letters to the editor were still mostly from men who often articulated anxieties about control over women as part of a conversation about their struggle to act as breadwinners under segregatory rule. It was also in the early 1930s that the growing network of African women's welfare societies entered public politics in Durban, not least through their successful opposition to plans by the municipality to impose a new system of pass laws on 'native' women. Exactly at this time the newspaper introduced an English-language 'Page for the Ladies' and invited contributions from educated women. At first it attracted no female writers and reproduced contemporary colonial tropes about proper and improper femininity. But in 1938 kholwa women who were active in Daughters of Africa created a new isiZulu language women's page. Growing numbers of women were also now writing letters to the editor to debate modern relationships and the gender politics of survival under segregationist rule. The women's page articulated ideas of public motherhood as part of an African nationalist discourse that pushed against narrowly patriarchal conceptions of the New African.